2018
DOI: 10.3389/fpsyg.2018.02565
|View full text |Cite
|
Sign up to set email alerts
|

Dilation and Constriction of Subjective Time Based on Observed Walking Speed

Abstract: The physical properties of events are known to modulate perceived time. This study tested the effect of different quantitative (walking speed) and qualitative (walking-forward vs. walking-backward) features of observed motion on time perception in three complementary experiments. Participants were tested in the temporal discrimination (bisection) task, in which they were asked to categorize durations of walking animations as “short” or “long.” We predicted the faster observed walking to speed up temporal integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 105 publications
(129 reference statements)
0
28
0
Order By: Relevance
“…Consistent with this change-based model of time perception, stimulus motion-or a change in the stimulus' spatial position over time-appears to be a fundamental cue in time perception. Several studies have shown that dynamic stimuli are perceived to last longer than static stimuli, and that fastmoving stimuli are perceived as longer in duration than slow-moving stimuli (Brown 1995;Kanai et al, 2006;Kaneko & Murakami, 2009;Kars¸ılar et al, 2018;Lhamon & Goldstone, 1975;Mate et al, 2009;Matthews, 2011).…”
Section: Contextual Influences Of Motion Direction On Time Perceptionmentioning
confidence: 99%
“…Consistent with this change-based model of time perception, stimulus motion-or a change in the stimulus' spatial position over time-appears to be a fundamental cue in time perception. Several studies have shown that dynamic stimuli are perceived to last longer than static stimuli, and that fastmoving stimuli are perceived as longer in duration than slow-moving stimuli (Brown 1995;Kanai et al, 2006;Kaneko & Murakami, 2009;Kars¸ılar et al, 2018;Lhamon & Goldstone, 1975;Mate et al, 2009;Matthews, 2011).…”
Section: Contextual Influences Of Motion Direction On Time Perceptionmentioning
confidence: 99%
“…The type and intensity of exercise performed has been shown to have an impact on time perception ( Edwards and McCormick, 2017 ; Hanson and Lee, 2017 ; Karsilar et al, 2018 ). Although the research on this topic is limited, the inaugural study conducted by Edwards and McCormick (2017) demonstrated the effects of time perception distortion with varying exercise intensities.…”
Section: Physiological Factorsmentioning
confidence: 99%
“…These results align with results from a study conducted by Hanson and Lee (2017) , where time seemed to pass by more slowly as a higher intensity was completed and a higher RPE was reported. Another study that examined walking speed as a measure of intensity demonstrated that with an increase in walking speed, time subjectively dilated (passed more slowly) ( Karsilar et al, 2018 ). Interestingly, the effect of exercise intensity on time perception was most prominent in long duration, endurance-type exercises (e.g., rowing ergometer tests) ( Edwards and McCormick, 2017 ).…”
Section: Physiological Factorsmentioning
confidence: 99%
“…As previous studies have shown that the physiological arousal accompanying any bodily activity dilates time judgments (see above, and Karşılar et al, 2018), we hypothesized that the lack of such physiological arousal in the passive condition would contract time estimates.…”
mentioning
confidence: 96%
“…For prospective duration judgments, a large body of evidence has shown that the more attention a task requires, the shorter is the estimated time (Matthews & Meck, 2016). Additionally, higher physical activity has been shown to prolong the estimates (Karşılar, Kısa, & Balcı, 2018;Sayalı, Uslu, Mencelo glu, Canbeyli, & Balcı, 2018). These findings can be explained by assuming that individuals have an internal clock system, such as in the Attentional-Gate Model (Block & Zakay, 1996), where arousal increases the pulse rate and an attentional gate regulates the accumulation of pulses through attentional resources.…”
mentioning
confidence: 99%